2014
DOI: 10.1134/s0001437014050105
|View full text |Cite
|
Sign up to set email alerts
|

Application of interleaving models for the description of intrusive layering at the fronts of deep polar water in the Eurasian Basin (Arctic)

Abstract: Interleaving models of pure thermohaline and baroclinic frontal zones are applied to describe intrusions at the fronts found in the upper part of the Deep Polar Water (DPW) when the stratification was absolutely stable. It is assumed that differential mixing is the main mechanism of the intrusion formation. Important parameters of the interleaving such as the growth rate, vertical scale, and slope of the most unstable modes relative to the horizontal plane are calculated. It was found that the interleaving mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
2
4
0
Order By: Relevance
“…Findings by Merryfield (2002) were confirmed by Kuzmina et al (2014). However, the 2-D model of interleaving driven by differential mixing at the baroclinic front failed to simultaneously fit three modeled parameters, namely, the vertical scale, the growth time, and the slope of the fastest growing mode, with observations of intrusions in a frontal zone with a substantial baroclinicity in the upper PDW layer (Kuzmina et al, 2014). In particular, it was found that the vertical scale of the most unstable mode was about 2 to 3 times smaller than the vertical scale of intrusions observed in the baroclinic front.…”
Section: Introductionsupporting
confidence: 57%
See 2 more Smart Citations
“…Findings by Merryfield (2002) were confirmed by Kuzmina et al (2014). However, the 2-D model of interleaving driven by differential mixing at the baroclinic front failed to simultaneously fit three modeled parameters, namely, the vertical scale, the growth time, and the slope of the fastest growing mode, with observations of intrusions in a frontal zone with a substantial baroclinicity in the upper PDW layer (Kuzmina et al, 2014). In particular, it was found that the vertical scale of the most unstable mode was about 2 to 3 times smaller than the vertical scale of intrusions observed in the baroclinic front.…”
Section: Introductionsupporting
confidence: 57%
“…Merryfield (2002) was the first to show satisfactory agreement between calculations of unstable modes from a three-dimensional (3-D) interleaving model that accounted for the differential mixing at a non-baroclinic front and observations of intrusive layering at a pure thermohaline front in the PDW. Findings by Merryfield (2002) were confirmed by Kuzmina et al (2014). However, the 2-D model of interleaving driven by differential mixing at the baroclinic front failed to simultaneously fit three modeled parameters, namely, the vertical scale, the growth time, and the slope of the fastest growing mode, with observations of intrusions in a frontal zone with a substantial baroclinicity in the upper PDW layer (Kuzmina et al, 2014).…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…5, bottom panel): the temperature decreases and salinity increases with depth. This structural feature of the mean thermohaline stratification is also common to the UPDW (Rudels et al, 1999;Kuzmina et al, 2011Kuzmina et al, , 2014.…”
Section: Smax=34mentioning
confidence: 63%
“…The absence of the main part of BSBW (with temperature less than -0.5°C) at longitudes to the east of 126°E may be due to various reasons, including mixing with the FSBW caused by thermohaline intrusive layering at stable-stable stratification (Merryfield, 2002;Kuzmina et al, 2013;Kuzmina et al, 2014;Kuzmina, 2016, Zhurbas N., 2018Kuzmina et al, 2018Kuzmina et al, , 2019. Indeed, according to numerous studies, the intrusive layering in the ocean determines the processes of exchange and mixing of various water masses (see, e.g., Stern, 1967;Fedorov, 1976;Joyce, 1980;Zhurbas et al, 1993;Rudels et al, 1999;Kuzmina, 2000;Walsh and Carmack, 2003).…”
Section: θ-S Analysismentioning
confidence: 99%